Evolution of virulence: malaria, a case study - Read, Andrew (Henry Stewart Talks, 2007)
Why are infectious agents virulent?, Evolutionary and mechanistic explanations, Natural selection on malaria virulence, Why are malaria parasites so virulent?, Why not more virulent?, Possible selective effects of public health interventions, Other infectious diseases, Why evolutionary explanation matters
Reviewed at 2020/08/16